Assessing activities on promoting fresh markets of Pattani municipality to be food safety centers youth with process Buddhist media application - Kewsuwun, Nawapon; Jeawkok, Jirachaya; Saengtong, Thanidaphat (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to assess activities regarding promoting the Pattani municipality’s fresh market to be a healthy food center. The key informants were 60 vendors and 480 customers. The researchers employed Health literacy evaluation, Eating behavior adjustment questionnaire, and semi-structured interviews as research tools also average, standard deviation, and content analysis as data analysis tools. The results are as followsThe vendors and customers of Chabangtikor fresh market and Pattani municipality fresh market demonstrated health literacy in the food aspect as an average level between 2.74 to 3.46 (¯x = 2.74 to ¯x = 3.46) and health knowledge as 71.9 to 90.2 percent.The key informants showed that there was an increase in every aspect in eating behavior adjustments as food sanitation; they adjusted a behavior on putting all food in frozen storage for 9.3 percent, environment; they sorted waste as garbage and trash for 7.7 percent, and behavior adjustment; they provided suggestions and answers precisely regarding selling food at the markets for 29.2 percent. Guidelines in promoting the markets as food safety centers and health safety behavior of the vendors as follows: 1. food sanitation, the vendors would produce food according to food safety guidelines, participation on investigating, following up, evaluating, and they should have been informed about food quality results 2. environment, the vendors should pay more attention to the market’s atmosphere by having Big Cleaning Day events and waste sorting and 3. health safety promoting, the venders should be concerned on serving their customers and cleanliness also healthpromoting activities for the vendors. The research results could be developed to be as parts of a policy regarding driving food safety for food vendors in the multicultural area and parts of a strategic plan, project, or solution on awareness of health, nutrition, and consumption safety including proper food-producing and selling in the multicultural area effectively.